PROBLEMATIKA ORANG TUA DALAM MEMBINA IBADAH SHALAT WAJIB ANAK USIA 10-12 TAHUN PADA ERA DIGITAL DI DUSUN SETAMBAH B, DESA SUNGAI RAMBAH KECAMATAN SAMBAS TAHUN 2023 - Nilawati Nilawati; Saripah Saripah; Mauizatul Hasanah (ADIBA : JOURNAL OF EDUCATION, 2025)
This study discusses the problems faced by parents in guiding their children aged 10-12 years to perform compulsory prayers in the digital era in Setambah B Hamlet, Sungai Rambah Village, Sambas District. The objectives of this study are to reveal: 1) To identify the challenges faced by parents in fostering compulsory prayer among children aged 10-12 years in the digital era in Setambah B Hamlet, Sungai Rambah Village, Sambas District in 2023. 2) To identify the strategies employed by parents to address the challenges in fostering the obligatory prayer practices of children aged 10-12 years in the digital age in Setambah B Village, Sungai Rambah Sub-district, Sambas District in 2023. This study employs a qualitative research method with a phenomenological approach. Three data collection techniques were used: observation, interviews, and documentation. Data analysis techniques include data reduction, data display, verification, and conclusion drawing. Data validity was ensured through triangulation and member checking. The results of this study indicate that: 1) The problems faced by parents in fostering the obligatory prayer of children aged 10-12 years in the digital era in Setambah B Hamlet, Sungai Rambah Village, Sambas District include: first, low parental understanding of religion, as indicated by the parents' educational attainment, which is only primary school, second, lack of parental role models in the family, especially in terms of worship, third, parents are busy working, as indicated by their daily activities as rubber and rice farmers who have little time to spend with their children, fourth, minimal supervision from parents due to work factors, resulting in reduced family togetherness, and finally, children are influenced by gadgets, as evidenced by their neglect of worship, even to the point of abandoning prayer. 2) The ways parents address challenges in fostering prayer among children aged 10–12 years in the digital era in Setambah B Village, Sungai Rambah Sub-district, Sambas District, include various forms of guidance: setting a good example (by directly demonstrating prayer to children), establishing habits (encouraging children to perform obligatory prayers), giving advice, (giving children daily advice on the importance of prayer), limiting gadget use (by setting time limits for children to use mobile phones), and imposing punishments (by giving children educational punishments, such as reprimanding them directly).